Prognostic factors impacting survival rates of hypopharyngeal cancer with nomogram prediction: a SEER-based study - Tawfik, Gehad Mohamed; Vuong, Nguyen Lam; Zayan, Ahmad Helmy; Abdelaal, Abdelaziz; Tieu, Thuan Minh; Sang, To Kim; Ebied, Amr; Shafik, Amr G.; Huy, Nguyen Tien (The Egyptian journal of otolaryngology, 2022)
Background We analyzed prognostic factors of hypopharyngeal carcinoma and developed a nomogram to predict survival rates in non-metastatic (M0) patients. Subjects and methods We included 4068 hypopharyngeal carcinoma patients identified from the Surveillance, Epidemiology, and End Results Program database between 2004 and 2015 in a retrospective cohort study. We analyzed prognostic factors of hypopharyngeal carcinoma using cause-specific and overall survival rates. We developed a nomogram to predict patients’ survival rates by multivariate Cox regression. Results Five-year survival rates of all stages between 2004 and 2010 were 25–35%. Radiotherapy pre- and post-surgery was the best modality of treatment according to 1-year and 5-year survival rates. The worst survival was in the posterior wall of the hypopharynx significantly ( HR s [95% CI ], P ) (1.238 [1.045–1.466], P = 0.013). The highest survival rate was for the combination of surgery and radiotherapy pre- and post-surgery compared to radiation pre-surgery (0.532 [0.231–1.225], P = 0.138). Our nomogram revealed a better predictive probability over the 6th AJCC-TNM classification for predicting 5-year overall survival. Conclusions The worst survival was old age hypopharyngeal carcinoma patients, with the primary site in the posterior wall of the hypopharynx. The best survival was linked to receiving radiotherapy pre- and post-surgery. Our nomogram revealed a better predictive probability over TNM classification for predicting 1- and 5-year overall survival, which enables clinicians to make better treatment recommendations.